2022
DOI: 10.1111/jocn.16236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of e‐health interventions on health outcomes in patients with rheumatoid arthritis: a systematic review and meta‐analysis

Abstract: Aims and Objectives To evaluate the effects of e‐health interventions on disease activity, self‐efficacy, pain and quality of life among patients with rheumatoid arthritis (RA). Background Prior systematic reviews have only reported the quality and features of e‐health interventions in patients with RA. However, the effect of e‐health interventions in patients with RA is unclear. Design Systematic review and meta‐analysis. Methods This review was conducted following the PRISMA guideline. We searched 5 database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Electronic intervention was reported to be ineffective for depression in 2 studies [ 51 , 60 ], whereas 3 articles [ 54 , 55 , 59 ] provided mixed conclusions. There were mixed results regarding the effect of pain relief, with some studies [ 50 , 51 ] indicating no effect on pain relief, and others [ 55 , 61 ] reporting the opposite. Seven studies reported on patient compliance: 2 studies [ 51 , 62 ] showed no statistical significance in improving patient compliance, 3 studies [ 63 - 65 ] showed a positive impact, and according to the remaining 2 studies [ 66 , 67 ], the impact was uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic intervention was reported to be ineffective for depression in 2 studies [ 51 , 60 ], whereas 3 articles [ 54 , 55 , 59 ] provided mixed conclusions. There were mixed results regarding the effect of pain relief, with some studies [ 50 , 51 ] indicating no effect on pain relief, and others [ 55 , 61 ] reporting the opposite. Seven studies reported on patient compliance: 2 studies [ 51 , 62 ] showed no statistical significance in improving patient compliance, 3 studies [ 63 - 65 ] showed a positive impact, and according to the remaining 2 studies [ 66 , 67 ], the impact was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Among the published systematic evaluations, studies on the application of electronic interventions included patients with cancer, respiratory diseases, and arthritis. In terms of quality of life, 3 studies [49][50][51] reported that electronic interventions were ineffective, but 7 [52][53][54][55][56][57][58] reported improvement in quality of life. Two articles [51,57] reported that electronic intervention was ineffective in relieving anxiety, and another [59] showed mixed views.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 1 more Smart Citation